Species distribution and susceptibility profile of Candida species in a Brazilian public tertiary hospital - Bruder-Nascimento, Ariane [UNESP] (2010)
Background. Species identification and antifungal susceptibility tests were carried out on 212 Candida isolates obtained from bloodstream infections, urinary tract infections and dialysis-associated peritonitis, from cases attended at a Brazilian public tertiary hospital from January 1998 to January 2005. Findings. Candida albicans represented 33% of the isolates, Candida parapsilosis 31.1%, Candida tropicalis 17.9%,Candida glabrata 11.8%, and others species 6.2%. In blood culture, C. parapsilosis was the most frequently encountered species (48%). The resistance levels to the antifungal azoles were relatively low for the several species, except for C. tropicalis and C. glabrata. Amphotericin B resistance was observed in 1 isolate of C. parapsilosis. Conclusions. The species distribution and antifungal susceptibility herein observed presented several epidemiological features common to other tertiary hospitals in Latin American countries. It also exhibited some peculiarity, such as a very high frequency of C. parapsilosis both in bloodstream infections and dialysis-associated peritonitis. C. albicans also occurred in an important number of case infections, in all evaluated clinical sources. C. glabrata presented a high proportion of resistant isolates. The data emphasize the necessity to carry out the correct species identification accompanied by the susceptibility tests in all tertiary hospitals. © 2010 Bagagli et al; licensee BioMed Central Ltd.